PROVIDING OF FUNCTIONING AND DEVELOPMENT OF MUNICIPALITIES - Yevdokimov , O.V. (The actual problems of regional economy development, 2020)
The purpose of the publication is to determine the planning mechanism for provision of needs of the united municipality. As the research methods, theoretical analysis and generalization of the domestic and foreign experience of the functioning of municipal formations were used. According to the results of the study, the mechanism of planning of the needs of the united territorial community, which allows maximizing the effectiveness of its socio-economic development with minimal financial infusions, is proposed. The scientific novelty of this publication consists in expanding the tools of planning current expenditures of local self-government related to providing the functioning of the community. The practical application of its results can potentially improve the efficiency of the process of providing the needs of inhabitants of the municipality.